Child talk relating parenting styles with the communication skills of children - Dalangin, Jose Adrian Jusi (2012)
"Parenting is vital to the development of children. Baumrind (1978) describes this activity as a determinant of a child's personality, character and competence and a role that cannot be evaded by parents (Baumrind,1978). A huge part of children's competence if communication skills development, especially after language acquisition for up to six (6) years. The style of parenting then is crucial during the developmental years of the child. This study focuses on how the different parenting style contribute to the communicative development of the child. It triangulates three data gathering methods: (1) focus interview, (2) direct observation and (3) communication skill test. The informants comprise twenty-three (23) sets of parents and their respective children. They were purposefully chosen to represent families across different socioeconomic groups, all coming from NCR and CALABARZON. After subjecting the information to open and thematic coding, the study revealed that there is no strong link between child rearing styles and communication skill development of children. This is due to the fact that the children vary in terms of their willingness to communicate, expressiveness, attentiveness and comprehension when compares to the styles employed by their parents. For further studies, the researchers recommend using alternative methodological approaches in data gathering and to look into different aspects and factors in communication development among children."